The importance of communication in the Integrated Medical Emergency System - Lázaro Armando Águila Trujillo; Mayelín Alomá Nohaya (Medisur)
Communication is a process involving two or more human beings who share their experiences, knowledge and feelings; entails the passage from isolated individual existence to community social existence. This process is of extraordinary importance in the Integrated Medical Emergency System, since calls are received from people with sick relatives, passers-by or health professionals who request a mobile emergency service for the care and transfer of a patient, so the people who work there must achieve an adequate and coherent verbal communication, according to the emergency situation that arises and, even, taking into account the emotional state of the caller. In the Cienfuegos province, with the objective of improving the communication of the staff who work in the system, a work algorithm is proposed to integrate already established actions, with others that were incorporated, including from their selection to their training, in order to prepare the members of the coordinating board to achieve an effective communication, which allows optimizing the service provided. The purpose of this research is to present a work algorithm to improve the staff communications who work in the system.